2008
DOI: 10.1145/1383602.1383647
|View full text |Cite
|
Sign up to set email alerts
|

Real women don't write programs

Abstract: Some universities are concerned about low levels of female enrolment in their computer science courses. This paper takes a humorous approach to this serious problem. The paper examines some of the barriers to female participation in computer science courses, especially in courses which involve programming. The paper then makes some suggestions for increasing female participation in computer science courses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Moreover, in programming, studies found that females can suffer from frustration, inadequacy, and a lower self-awareness level than males when working on a similar coding project (Kemp et al, 2020 ), a finding that would explain the gender and performance gaps. Other studies reported that programming careers are more dominant by men, and women do not excel in programming or show an interest in learning to program (Contreras-Ortiz et al, 2021 ; Edmondson, 2008 ). Recommendations to improve the performance gap include upgrading course design and focusing on pedagogy, as studies showed that females favour problem-based learning, in-class discussions, and group work (Wagner, 2016 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, in programming, studies found that females can suffer from frustration, inadequacy, and a lower self-awareness level than males when working on a similar coding project (Kemp et al, 2020 ), a finding that would explain the gender and performance gaps. Other studies reported that programming careers are more dominant by men, and women do not excel in programming or show an interest in learning to program (Contreras-Ortiz et al, 2021 ; Edmondson, 2008 ). Recommendations to improve the performance gap include upgrading course design and focusing on pedagogy, as studies showed that females favour problem-based learning, in-class discussions, and group work (Wagner, 2016 ).…”
Section: Literature Reviewmentioning
confidence: 99%